Rock-typing of laminated sandstones by nuclear magnetic resonance in the presence of diffusion coupling - Alhwety, Nader H.; Sayedakram, Nawaf I.; Shikhov, Igor; Arns, Christoph H. (Diffusion Fundamentals, 2014)
In this work, the aim is to assess the relative importance of the impact of diffusional coupling on NMR measurements of saturated laminated sandstone numerically at the layer scale to assess the feasibility of NMR rock-typing approaches. We use two 3D model structures based on a Boolean particle process, providing a range of structural to diffusion length ratios to explore the relationships between pore geometry, surface magnetic properties, and NMR transverse relaxation time. The influence of surface relaxivity and bulk susceptibility contrast on T2 relaxation responses is tested for layered structures to improve the rock-typing methodology. An escalation in pore coupling is observed with decreasing bed thickness as well as decreasing bulk susceptibility contrast and surface relaxivity the latter ones reducing the time available for pore coupling by reducing the effective relaxation rate. When pore coupling is strong, the T2 distribution clearly misrepresents the underlying bimodal distribution of the different morphologies. Consequently, the bimodal relaxation time becomes merged and the relative amplitude of the peaks fails to reflect the true morphologies of the models. Furthermore, we observed that in low noise conditions of numerical simulation the effect of diffusional coupling on transverse relaxation may be misinterpreted for the regularization effect on ILT solution. In such cases, careful selection of Laplace inversion method is essential for effective rock-typing by NMR.